(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to explain the practice of fine motor learning management carried out, identify the obstacles faced by teachers and education personnel in implementing fine motor learning management, and analyze the role of the school environment in supporting fine motor learning management at TK Aisyiyah Wuled, RA Wuled, and BA Wuled, Tirto District, Pekalongan Regency in January 2024-June 2024. This study is expected to contribute to the development of early childhood education theory, as well as become a basis for further research on the effect of fine motor learning on child development. This study uses a qualitative method with in-depth interview techniques, participatory observation, and documentation studies. Interviews were conducted with teachers, principals, and parents, while participatory observation was conducted during learning activities. The results of the study indicate that fine motor learning management at TK Aisyiyah Wuled, RA Wuled, and BA Wuled is carried out by considering the stages of child development and using an approach that focuses on active learning, creativity, and innovation. The main obstacles faced by teachers and education personnel are lack of time to prepare materials, lack of human resources, and high costs to purchase needed goods. A conducive school environment such as adequate facilities, parental support, and environmental safety contribute to the success of fine motor learning management. This study provides practical benefits in the form of recommendations for improving teaching practices, improving the quality of early childhood education, supporting policy making, and empowering school communities. The results of the study also provide new perspectives on the real challenges in implementing fine motor learning in early childhood education environments.